Model Partisipasi Petani dalam Pengembangan Agrowisata di Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - SURYAWAN, I WAYAN DEDI; WINDIA, I WAYAN; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p11, 2018)
Farmers Participation Model in Agrowisata Development in Kerta Village, Payangan District, Gianyar Regency. The model of farmer participation in agro-tourism development in Kerta Village, Payangan District, Gianyar Regency is an effort to find out the model of farmer participation and farmer participation level in agro-tourism development. The research location is in Kerta Village, Payangan District, Gianyar Regency which is an agro area of Gianyar Botanical Garden. The method of analysis used is descriptive qualitative. The results showed that the farmers participation model is as follows. (a) Aspects of mindset; farmers are aware of the potential that exists in Kerta Village that can be developed as agro-tourism. (b) Social aspects; farmers' participation in social aspects such as participating in garden arrangement, diversification of commodity diversity, there is also agreement or cooperation between farmer society to sacrifice their land for agro-tourism such as for road and treking. (c) Aspects of artifacts / possessions; peasant community participation in view of the material aspects include the garden and agricultural products, huts / huts for rest, parking lots and public toilets. Farmers participation rate is as follows. (a) Manipulation; done by changing the attractiveness of the attraction of organic citrus quotes. (b) Dissemination of information; the peasant community conveys information to the general public through word of mouth, social media, billboards installation. (c) Decision-making; demonstrated by their active ngrembug to reach joint decisions and participate in village deliberations. (d) Building agreements; farmers mutually respect opinion in decision-making to build a deal based on "Tri Sakti". Suggestion for farmer community to keep participating for agrotourism development in Kerta Village, considering the enormous potential of agriculture to be developed into agro-tourism area. Through the model of farmer participation in agrotourism development in Kerta Village, Payangan District, Gianyar Regency, can be used as a reference for agro-tourism development in other regions.